Combination of Thermochemical Energy Storage and Small Pressurized Water Reactor for Cogeneration System. (May 2015) - Ishitobi, Hirokazu; Ryu, Junichi; Kato, Yukitaka
Abstract: In recent decades, small nuclear reactors for cogeneration systems have been studied. Generally, nuclear plants are operated at steady state, but the heat demand load is not steady. Load leveling using thermochemical energy storage (TcES) is a potential method for overcoming this problem. In this work, the heat load of a town was assumed, and the required amount of TcES material for load leveling was estimated. The amount of material required, relative to the volume of the nuclear reactor vessel, was acceptable for installing a TcES system at the nuclear plant.